Classification of experimental acute pain intensity with multimodal biosignals - Syrjälä, Elise (fi=Turun yliopisto|en=University of Turku|, 2017)
Pain is an unpleasant sensation associated with an emotional experience. To provide an effective and safe pain treatment, accurate pain assessment is required. Until today, no adequate methods have been available to reliably detect or assess pain. Earlier studies have shown that some of the most common non-verbal features of acute pain include are facial grimaces and signs of increased autonomic activity. This thesis introduces a preclinical study where multimodal biosignals were collected from 31 healthy volunteers to build up a composite signal which would be as close to a pain-specific measure as possible. Continuous measurements of physiological parameters (heart rate, respiratory rate and galvanic skin response) were used together with several facial surface electromyography (sEMG) signals to classify three levels of self-reported pain intensity (no pain, mild pain, moderate/severe pain). Acute pain was simulated with a slowly increasing heat or electrical stimulus induction. Physiological signals were obtained as one value per second density, no additional feature extraction was performed. Facial sEMG values were adjusted with down sampling from the collection frequency of 1000 Hz to analysis frequency 1Hz with root mean square transformations. Meta-analysis was performed with kNN nested leave-one-subject-out (LOSO) cross-validation (CV). The final kNN analysis with non-nested LOSO CV showed 0.829 and 0.827 concordance on subject and test level self-reported pain intensity, respectively. Classification of experimental acute pain intensity with the composition of multimodal biosignals shows very promising results. The pain related quantitative measures, such as biosignals, provide valuable information. Combining further studies of the signals with the development of machine learning algorithms best suitable for this domain, brings us closer to more reliable pain assessment and better pain management.

Kipu on epämiellyttävä aistikokemus, johon liittyy tunneperäinen elämys. Tehokas ja turvallinen kivunhoito vaatii tarkkaa kivun arviointia. Toistaiseksi ei ole olemassa riittävän hyviä menetelmiä, joilla kipu havaitaan tai voidaan arvioida luotettavasti. Aiemmat tutkimukset ovat osoittaneet, että akuutin kivun tavallisimpiin nonverbaalisiin piirteisiin kuuluvat irvistys kasvoilla ja autonomisen aktiivisuuden lisääntymisen merkit. Tämä tutkielma esittelee prekliinisen tutkimuksen, jossa keräämällä multimodaalisia biosignaaleja 31:ltä terveeltä vapaaehtoiselta, rakennettiin komposiittisignaali, joka vastaisi mahdollisimman hyvin kipu-spesifistä mittausta. Kolmea kipuastetta (ei kipua, lievä kipu, kohtalainen/kova kipu) luokiteltiin jatkuvasti mitattavien fysiologisten parametrien (sydämen syke, hengitystiheys, galvaaninen ihoreaktio) sekä useiden kasvojen pinnallisten elektromyografisten mittausten avulla. Akuuttia kipua simuloitiin aiheuttamalla hitaasti lisääntyvää lämpö- tai sähköstimulaatiota. Fysiologisia signaaleja käytettiin sekunnin tarkkuudella, ilman lisäpiirteiden luomista. Kasvojen sEMG-arvot säädettiin keräystaajuudesta 1000 Hz analyysitaajuuteen 1 Hz neliöllisen keskiarvon (RMS) muunnoksella. Meta-analyysi tehtiin kNN-menetelmä käyttäen nestatulla, henkilöittäin ositetulla (LOSO), ristiinvalidoinnilla. Lopullinen kNN-analyysi, joka suoritettiin ei-nestatulla LOSO-ristiinvalidoinnilla, tuotti 0.829 ja 0.827 konkordanssin henkilö- sekä testitasolla mitattuina. Kokeellisen akuutin kiputason luokittelu multimodaalisten biosignaalien kompositiolla osoittaa hyvin lupaavia tuloksia. Kipuun liittyvät kvantitatiiviset mittaukset, kuten biosignaalit, tuottavat arvokasta informaatiota. Tätä tietoa eteenpäin tutkimalla ja sille parhaiten sopivia koneoppimisalgoritmeja kehittämällä pääsemme lähemmäs luotettavampia kivun arviointimenetelmiä ja parempaa kivun hallintaa.